Morphological and anatomical characteristics, and qualitative analysis of phytochemicals of costus specciosus (koen.) sm.), costaceae family - Le, Văn Út (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Costus specciosus (Koen.) Sm. (Zingiberaceae) has proved to be effective in the treatment of diabete và cholesterol levels. However, the document of morphological and anatomical characteristics of this species in Viet Nam is still negligible. It is necessary to establish the document of morphological and anatomical characteristics of this species. To investigate the morphological and anatomical characteristics as well as to qualitatively analysis the bioactive ingredients in Costus specciosus (Koen.) Sm. province were performed for plant identification. The scientific name of species was determined by comparison of morphological and anatomical characteristics with those in the reported documents. Morphological and anatomical characteristics of used parts of Costus specciosus (Koen.) Sm. was analysed, described and photographed. Beside that, the bioactive ingredients in Costus specciosus (Koen.) Sm. was analysed. The results so that: Morphology: Stems more or less woody at base, unbranched, spirally twisted in upper part. Flowers regular, bisexual, 3 merous. Anatomy: Root - Cylindrical, divided into two distinct regions, the cortical region is larger than the cylindrical region. Stems - Cylindrical and convex outer contour. Rhizomes, stem and leaves of Costus specciosus (Koen.) Sm. contain carbohydrats, coumarins, flavonoids, saponins, proteins and amino acid.